Common Errors in Using Conjuction - Natasya, Natasya; Lubis, Yani; Siregar, Suci Romadhani; Rambe, Riza Hamdani (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
Errors in conjunction usage remain a significant challenge for English as a Foreign Language (EFL) learners, adversely impacting textual cohesion, coherence, and overall writing quality. This study aimed to identify common conjunction-related errors, analyze their underlying causes, and evaluate strategies to address them. The research employed a quasi-experimental design involving 60 EFL learners divided into experimental and control groups. The experimental group received instruction integrating context-based teaching, corpus-based learning, and structured formal writing practice, while the control group followed a traditional grammar-focused approach. Pre-test and post-test assessments evaluated improvements in conjunction usage accuracy, textual cohesion, and error reduction. Findings revealed that conjunction errors frequently disrupted text meaning, diminished academic performance, and created negative impressions of writer proficiency. Contributing factors included mother tongue interference, limited grammatical understanding, insufficient writing practice, and theoretical teaching methods. The integration of innovative instructional strategies significantly improved conjunction usage, as evidenced by increased accuracy and enhanced cohesion and coherence in the experimental group’s written texts. This study underscores the importance of adopting context-driven teaching strategies to address conjunction-related errors, with implications for EFL instruction and curriculum design. Further research is recommended to explore these methods across broader learner demographics and linguistic contexts.